Introducing the Model of Factors Influencing Knowledge Sharing Departments OF Islamic Azad University (Survey in the North Branch of Tehran and Science and Researches Campus) - Zahra Alipour Darvishi (Journal of Information Technology Management)
The ability of knowledge sharing is an important prerequisite to achieve educational and research competence in the academic departments. This paper aims to determine the factors affecting knowledge sharing within and between departments in Islamic Azad University. Technological capabilities, organizational culture, organizational structure, knowledge documentation, supervision control, organizational interaction, relational involvement and motivational methods are the organizational contextual factors as well as the perceptual factors including trust in management, fear of loosing one’s unique value and perceived organizational support, all of the above mentioned have been tested as the independent variables. This survey research was implemented within North Branch of Tehran and Science and Researches Campus including 148 stratified random samples of the faculty members. The statistical analysis of the model has been done through one sample T-test, confirmatory factor analysis & structural equation model with SPSS and PLS software’s. These results are defined as trust in management has significant effect on knowledge sharing within and between departments with mediation effect of knowledge documentation. Technological capabilities and perceived organizational support have significant effect on knowledge sharing among departments. Also the material and spiritual motivational methods have significant effect on knowledge sharing within departments. In order to promote knowledge sharing the results of this research has provided the empirical basis for planning and implementing knowledge management mechanisms in universities.